Hemiplegic-Migraine–like Attacks as First Manifestation of Diffuse Leptomeningeal Glioneuronal Tumor: A Case Report. Issue 3 (3rd April 2022) - Fetta, Anna; Pruccoli, Jacopo; Biasucci, Giacomo; Parisi, Roberto; Toni, Francesco; Melchionda, Fraia; Cordelli, Duccio M.
Abstract : Background: Diffuse leptomeningeal glioneuronal tumor (DLGNT) is a low-grade tumor characterized by diffuse leptomeningeal infiltrates. Symptoms are usually secondary to hydrocephalus. Hemiplegic migraine (HM)-like episodes have never been associated with DLGNT, but they have been reported with different inflammatory and tumoral entities involving leptomeninges. Observations: We report the case of a 10-year-old boy with recurrent episodes of right hyposthenia, aphasia, and headache lasting hours to days with complete remission. The electroencephalogram during the attack showed diffuse slower activity on the left hemisphere, which improved together with the symptoms. DLGNT was discovered during a follow-up magnetic resonance imaging and confirmed by biopsy. Conclusions: This is the first report of HM-like attacks in DLGNT. We discuss the pathogenetic hypotheses of our case and previously reported cases of "symptomatic" HM with leptomeningeal involvement.